A Study of Neural Networks based Blackhole Attack Protection in WSNs - Vinothini, G (International Journal of Computer Sciences and Engineering, 2025)
A Wireless Sensor Network (WSN) is a collection of sensor nodes, which builds up a network using radio communication in an autonomous. This spoofing technique can be executed using blackhole or sinkhole attacks, which are used to fetch the streams of data leading to cluster heads or base stations usually. In this paper, we are addressing the issue of a variant of DDoS attack: Selective-Jamming Attack as TDMA is prone to a particularly insidious form of jamming attack, namely Selective Jamming (SJ).